Significado del saber popular en alimentación en un grupo de nutricionistas dietistas (2007)
ABSTRACT: To understand the meaning that nutritionist has of the folk knowledge about feeding. Methods: This is a qualitative study with a group of 34 nutritionists from the Metropolitan Area of the Valle del Aburrá (Medellin-Colombia), belonging to governmental and not governmental entities, who work in educational programs of health promotion. Conclusions: this study found that Nutritionist-Dieticians receive influence from the biomedical western medicine model in their professional training. Although nutritionists appreciate folk knowledge; they feel that it is a barrier for their professional practice, and for this reason they prefer to work under the traditional biomedical model, which does not allow establishing real communication between them and the people who they are working with.